2008
DOI: 10.1158/1078-0432.ccr-08-1841
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Expression Is an Independent Predictor of Poor Prognosis in Colon Cancer

Abstract: Purpose: Cyclooxygenase-2 (COX-2; PTGS2) is considered to play an important role in colorectal carcinogenesis and is often up-regulated in colon cancers. However, previous data on the influence of COX-2 expression on patient outcome have been conflicting. Experimental Design: Using 662 colon cancers (stage I-IV) in two independent prospective cohorts (the Nurses' Health Study and the Health Professionals Follow-up Study), we detected COX-2 overexpression in 548 (83%) tumors by immunohistochemistry. Cox proport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
138
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(149 citation statements)
references
References 47 publications
5
138
1
2
Order By: Relevance
“…Hence, we were able to confirm results from previous, smaller scale studies in UM 22,23 and other malignancies. [30][31][32] In summary, a higher immunoreactivity score for COX-2 staining was associated with a worse OS. In contrast to previous studies on UM, we observed no correlation between high COX-2 expression and the prevalence of the epitheloid cell type.…”
Section: Discussionmentioning
confidence: 82%
“…Hence, we were able to confirm results from previous, smaller scale studies in UM 22,23 and other malignancies. [30][31][32] In summary, a higher immunoreactivity score for COX-2 staining was associated with a worse OS. In contrast to previous studies on UM, we observed no correlation between high COX-2 expression and the prevalence of the epitheloid cell type.…”
Section: Discussionmentioning
confidence: 82%
“…Cyclooxygenase-2 is also considered to have an important role in colorectal carcinogenesis. Recently, Ogino et al (2008) reported that Cox-2 overexpression is associated with worse survival among colon cancer patients. Nuclear factor-kB is an end point of the TLR4/ MyD88 signalling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 is related to the formation of carcinogens, tumor promotion, apoptosis inhibition, angiogenesis development, and metastatic process (Meric et al, 2006). Up-regulation of expression of COX-2 has been associated with human intestinal inflammation, colorectal cancer (Wang and Dubois, 2010) and worse survival among CRC patients (Ogino et al, 2008). Therefore, COX-2 expression may be used to monitor the process of carcinogenesis, and the suppression of COX-2 expression can become a target for cancer chemoprevention (Singh et al, 1997).…”
Section: Discussionmentioning
confidence: 99%